Teenage Pregnancy and Opportunities in Latin America and the Caribbean : On Teenage Fertility Decisions, Poverty and Economic Achievement - Azevedo, Joao Pedro; Favara, Marta; Haddock, Sarah E.; Lopez-Calva, Luis F.; Muller, Miriam; Perova, Elizaveta (World Bank, Washington, DC, 2014)
The pregnancy project sought to expose the existence, and challenge the validity, of stereotypes about Hispanic women. The charade explored the underlying motivations of the many who responded with a wide range of reactions. The specific objectives of this regional study are: to establish a thorough description of the magnitude of the issue and its potential implications for social advancement; to advance the understanding of the risk factors, motivations and impacts at the household level-as a determinant of poverty and a cause of intra-and intergenerational poverty traps; to illuminate the coping mechanisms and their individual and social implications; to highlight the gender-related issues that have historically provoked asymmetric costs to boys and girls; and to provide elements that support specific policies on this matter. In the last decade, Latin America and the Caribbean (LAC) have been moving in the right direction and the region has experienced important gains in gender equality of endowments (assets) and economic opportunities. In most LAC countries, girls have been achieving gender parity in primary school enrollment and even outperforming boys at the secondary and tertiary level. The present report reviews the factors associated with teenage pregnancy and early childbearing and builds a framework to explore these issues systematically, towards the design of effective policy interventions in LAC. Teen pregnancy and early childbearing remain a challenge in the region, particularly given the association of these phenomena with poverty and lack of opportunities, and the concern that it may prevent women from taking full advantage of their human development assets and opportunities. The main message of the report is that poverty and lack of opportunities are key factors associated to early childbearing.